Characterisation and preliminary bioactivities of actinobacteria isolated from selected soil samples from Signy Island, Antarctica / Shoba Mary Thomas - Shoba Mary , Thomas (2018)
Actinobacteria are one of the most prominent bacterial groups, even in harsh Antarctic environments, with important functional roles in soil. Signy Island, part of the South Orkney Islands archipelago in Maritime Antarctica, provides a unique environment due to its isolation and simple ecosystems which allow a deeper look into the effects of warming on actinobacterial communities particularly as this region is experiencing a trend of warming temperatures. This unique ecosystem is also a valuable source of potential new bioactive products and bacterial species. Aside from this, the harsh environment exerts some selection pressure favouring bacteria capable of adapting and thriving by utilizing diverse substrates at lower temperatures. This study uses actinobacteria isolated from the soils of Signy Island for assays of enzyme and biosurfactant production at low temperatures. Through this, it was found that certain strains were producing enzymes at low temperatures indicating a possible production of cold-active enzymes. This production is an advantageous adaptation of actinobacterial strains to the polar environment. This study also describes a novel actinobacterial species isolated from Signy Island. The new species, strain S63, shares a less than 97 % similarity with Humibacillus xanthopallidus KV-663T; which is the only species in the genus. The whole genome of the strain has been sequenced and the draft genome shows the presence of genes coding for various stress tolerances. Phenotypic characterisation of the strain also evidences the potential of this strain being a novel species and genus of the family Intrasporangiaceae.